Beyond denitrification: The role of microbial diversity in controlling nitrous oxide reduction and soil nitrous oxide emissions. (14th March 2021) - Shan, Jun; Sanford, Robert A.; Chee‐Sanford, Joanne; Ooi, Sean K.; Löffler, Frank E.; Konstantinidis, Konstantinos T.; Yang, Wendy H.
Abstract: Many biotic and abiotic processes contribute to nitrous oxide (N2 O) production in the biosphere, but N2 O consumption in the environment has heretofore been attributed primarily to canonical denitrifying microorganisms. The nosZ genes encoding the N2 O reductase enzyme, NosZ, responsible for N2 O reduction to dinitrogen are now known to include two distinct groups: the well‐studied Clade I which denitrifiers typically possess, and the novel Clade II possessed by diverse groups of microorganisms, most of which are non‐denitrifiers. Clade II N2 O reducers could play an important, previously unrecognized role in controlling N2 O emissions for several reasons, including: (1) the consumption of N2 O produced by processes other than denitrification, (2) hypothesized non‐respiratory functions of NosZ as an electron sink or for N2 O detoxification, (3) possible differing enzyme kinetics of Clade II NosZ compared to Clade I NosZ, and (4) greater nosZ gene abundance for Clade II compared to Clade I in soils of many ecosystems. Despite the potential ecological significance of Clade II NosZ, a census of 800 peer‐reviewed original research articles discussing nosZ and published from 2013 to 2019 showed that the percentage of articles evaluating or mentioning Clade II nosZ increased from 5% in 2013 to only 22% in 2019. The census revealed that the slowly spreading awareness of Clade II nosZ may result in part from disciplinary silos, with the percentage of nosZ articles mentioning Clade II nosZ ranging from 0% in Agriculture and Agronomy journals to 32% in Multidisciplinary Sciences journals. In addition, inconsistent nomenclature for Clade I nosZ and Clade II nosZ, with 17 different terminologies used in the literature, may have created confusion about the two distinct groups of N2 O reducers. We provide recommendations to accelerate advances in understanding the role of the diversity of N2 O reducers in regulating soil N2 O emissions. Abstract : We present a new paradigm of controls on soil nitrous oxide (N2 O) emissions that accounts for N2 O reduction beyond the traditional focus on denitrification and Clade I N2 O reducers. Based on a synthesis of current knowledge about Clade I N2 O reducers and the more recently described Clade II N2 O reducers, we propose a conceptual framework for considering how microbial diversity may control N2 O emissions. Based on a census of peer‐reviewed articles discussing nosZ and published during 2013–2019, we make recommendations to accelerate progress in understanding the roles of taxonomic and functional diversity in controlling N2 O reduction rates and N2 O emissions